JMJD6 and U2AF65 co-regulate alternative splicing in both JMJD6 enzymatic activity dependent and independent manner. Issue 6 (28th November 2016) - Yi, Jia; Shen, Hai-Feng; Qiu, Jin-Song; Huang, Ming-Feng; Zhang, Wen-Juan; Ding, Jian-Cheng; Zhu, Xiao-Yan; Zhou, Yu; Fu, Xiang-Dong; Liu, Wen
Abstract: JMJD6, a jumonji C (Jmj C) domain-containing protein demethylase and hydroxylase, has been implicated in an array of biological processes. It has been shown that JMJD6 interacts with and hydroxylates multiple serine/arginine-rich (SR) proteins and SR related proteins, including U2AF65, all of which are known to function in alternative splicing regulation. However, whether JMJD6 is widely involved in alternative splicing and the molecular mechanism underlying JMJD6-regulated alternative splicing have remained incompletely understood. Here, by using RASL-Seq, we investigated the functional impact of RNA-dependent interaction between JMJD6 and U2AF65, revealing that JMJD6 and U2AF65 co-regulated a large number of alternative splicing events. We further demonstrated the JMJD6 function in alternative splicing in jmjd6 knockout mice. Mechanistically, we showed that the enzymatic activity of JMJD6 was required for a subset of JMJD6-regulated splicing, and JMJD6-mediated lysine hydroxylation of U2AF65 could account for, at least partially, their co-regulated alternative splicing events, suggesting both JMJD6 enzymatic activity-dependent and independent control of alternative splicing. These findings reveal an intimate link between JMJD6 and U2AF65 in alternative splicing regulation, which has important implications in development and disease processes.